Potensi Peternakan Ayam Buras Sebagai Usaha Ekonomi Masyarakat Pedesaan Di Provinsi Sumatera Barat - Rahmi Wati (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
This paper discussed the potency of kampong chickens as the main source of employment and income in West Sumatra. From about 2 millions of Indonesian kampong chickens in 2005, about 5.725.515 were found in West Sumatra. In terms of egg production, body weight gain and feed utilization efficiency, the productivity and biological performances of kampong chickens were much lower than that of hybrid chickens. On the other hand, the product of kampong chickens, e.g. egg and meat, in the market were normally valued higher by the consumers because of their better taste and healthier product. In addition, kampong chickens could be intensively reared in lower production cost because of their lower nutritional and management requirements. Results of some studies has shown that production of kampong chicken might be directed for business unit as back yard or intensively farming especially in supporting of economic development in the rural community.